A Statistical Technique for Analytical Review - Stringer, Kenneth W. (Journal of Accounting Research, 1975)
As a background for the subject of this paper I will present several quotations from section 320 of the Statement on Auditing Standards No. 1 (henceforth SAS No. 1), which was issued in November 1972 by the Committee on Auditing Procedure of the American Institute of Certified Public Accountants. This Committee was the predecessor of the present Auditing Standards Executive Committee and SAS No. 1 was its final pronouncement. SAS No. 1 is a codification of previous Statements on Auditing Procedure (SAPs) Nos. 33 through 54, and No. 33 in turn was a codification of prior Statements. Section 320 of SAS No. 1 is primarily a codification of SAP No. 54, which included as an appendix a report issued by the AICPA Committee on Statistical Sampling in July 1964.1 subject of section 320 is The Auditor's Study and Evaluation of Internal Control, but the last major topic in the section deals with the correlation of such evaluation with other auditing procedures. I believe that section, together with the two related appendixes, provides the most concise but complete statement of the broad conceptual framework for auditing that is presently available in official pronouncements. Many of the concepts expressed in that section are readily adaptable to restatement in the form of partial or complete mathematical models and to application by means of statistical methodology, which is the general theme of this conference. It is for these reasons that I draw on this source to provide perspective for the subject of this paper.